METHODOLOGICAL FOUNDATIONS OF THE FORMATION OF INDEPENDENT EDUCATIONAL COMPETENCE OF STUDENTS TEACHING ENGLISH AT LAW UNIVERSITIES - Shaakhrarovna, Aripova Shakhnoza (International Journal of Psychosocial Rehabilitation, 2020)
In this article describes features of organizing independent work of students at Tashkent State University of Law in the conditions of modular teaching of the methodological foundations of the formation of independent educational competence of students teaching English language at law Universities. Theoretical analysis of existing classifications of types of independent work is given. The concept of independent work in the process of learning English on a modular basis is proposed.